Between Claim and Practice: Delegating the Function of Adolescent Character Formation in Rural Families in Jeneponto - Jusmaliah J; Maria Ulfa; Syamsul Bakri; Risnawati Hannang (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Adolescent character formation is commonly studied as a normative role of the nuclear family, while the distance between the role that is claimed and the practice that is actually carried out is rarely examined. This article explores how parents in a rural hamlet in Jeneponto Regency, South Sulawesi, articulate responsibility for adolescent character formation, and how they describe their own practice. The study employs a single-site qualitative approach, using semi-structured interviews and observation involving thirteen participants comprising parents, adolescents, and local religious actors. Data were analysed thematically with source triangulation across role groups. Three findings emerge. First, participants consistently locate character formation as the primary responsibility of the nuclear family. Second, in the practice they themselves acknowledge, part of this function is carried out by other parties, namely residential religious educational institutions, extended family, and local religious actors. Third, participants link this transfer to livelihood demands, communication gaps with their children, the assumption that adolescents can already judge for themselves, and the absence of parenting guidance and adolescent development forums in their surroundings. In two participants, the normative statement and the admission of reduced involvement appeared within the same interview session. These findings offer functional delegation as a lens for reading caregiving practice in rural communities, while indicating that family strengthening programmes targeting parental knowledge alone risk missing the actors who actually perform the function.